Böhler’s and Gissane’s Angles of the Calcaneus in Bangladeshi Male - Islam, AHM Mazharul; Naushaba, Humaira; Akter, Tahmina; Jebin, Suraiya; Moin, Sharna; Singha, Partha Sarathi (Bangladesh Journal of Anatomy, 2018)
Context: Böhler’s angle and Gissane’s angle are commonly used to evaluate the severity of a calcaneal fracture and the goal of a surgical treatment is to restore these angles to normal values. Since the calcaneus is a weight bearing bone the calcaneal angles can possibly vary in different races due to variation in built and load bearing. Many studies were carried out in various populations to determine normal values of Böhler’s angle and Gissane’s angle. However, there is no published article on this topic in Bangladesh. So, this study was aimed to establish the standard data of Böhler’s angle and Gissane’s angle in adult Bangladeshi male and to make comparison with previous studies on other populations. Materials & Methods: Digital radiographs of left foot in lateral view in bilateral standing position were taken from 50 consented male students of Sir Salimullah Medical College, Dhaka aged between 21 to 26 years without any history of foot deformities and injuries. These radiographs of foot were imaged with a digital camera according to scale and were transferred to a computer. From these images Böhler’s angle and Gissane’s angle were measured by MB ruler software. Results: The mean±SD of Böhler’s angle and Gissane’s angle were 34.85±6.87° and 111.03±9.48° respectively. Bangladesh Journal of Anatomy July 2018, Vol. 16, No. 2, pp. 27-31